Electromyographic researches in the process of improvement of sport training management at sportswomen which specialized in athletic running jump. - Kutek T.B (Kharkov National Pedagogical University, 2011)
The represented of electromyography method gives an opportunity to purposeful control the degree technical skill of sportswoman by means to study of the between intermuscular coordination at taking the running jump and the spring-off in the high running jump. The employing electromyography method efficiency by means of the degree utilization speed-and-force capabilities the possibility at taking the spring-off gives an opportunity to evaluate the degree technical skill sportswoman and choice particular effect the most rationality of training exercises.